Marcas teatrais: artimanhas discursivas em narrativas de Sérgio Sant'Ana - Meira, Ana Caroline de Oliveira (2014)
This dissertation presents a study about the writer Sérgio Sant Anna (1941), native of Rio de Janeiro, owner of a complex and innovator literary project that ends up ensuring him a prominent place among the great names of Brazilian contemporary literature. Taken as ―disharmonic‖ regarding the classifications of genre established by the literary canon, his works, guided on inventiveness and experimentation, build up themselves from dialogues established among the various forms of art, from metafictional strategies and from the desire of the author in transgress the limits of the narrative traditional forms, which makes his readers, as well as the literary critics, question even the literary genre itself. And it is from the analysis of the literary works of this writer, most precisely the narratives Um romance de geração: comédia dramática em um ato (1981), A tragédia brasileira: romance-teatro (1987) e Um crime delicado (1997), especially the dialogue they establish with theatre, that this study aims to investigate how the peculiarities of the literary project of the writer, as well as the disruption with structural patterns and the inventive experimentation, singularizes him in the scene of contemporary Brazilian literature.